Personal Data Vulnerability in the Digital Era: Study of Modus Operandi and Mechanisms to Prevent Phishing Crimes - Flea Akbar Permana; Ahmad Jamaludin (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2023)
Rapid digital transformation has significantly increased the vulnerability of personal data, leading to an alarming increase in phising crimes. This scholarly article aims to investigate the modus operandi and prevention mechanisms of phising crimes in the era of digital transformation. Phising, a fraudulent practice that aims to obtain sensitive information through fraudulent means, has become a common cybercrime, targeting both individuals and organizations. This research utilizes a comprehensive literature review and analysis of various phising attack scenarios to identify common strategies used by cybercriminals. This analysis focuses on the techniques used to manipulate unsuspecting victims, such as social engineering, email forgery, and website forgery. In addition, this research explores the exploitative nature of data breaches and their implications for personal privacy. This article highlights the importance of collaboration between stakeholders, including government agencies, technology providers and individuals, in addressing the issue of personal data vulnerability. By sharing information, resources and best practices, stakeholders can work together to improve cybersecurity measures and effectively protect personal data. The findings from this study provide valuable insights into the modus operandi of phising crimes and the prevention mechanisms needed to protect personal data. By understanding the strategies used by cybercriminals and implementing proactive measures.